Optical range finder base don position sensitive detector - Mosquera L., Luis (2007)
A range finder is any device capable of measuring the distance between two points. An red laser pulsing at one Kflz is used as the light source, which is incident on a target. A PSD based optical receiver collects the reflected light from the target. The PSD produces two current signals that are amplified and passed through a band pass filter. The two signals are read by two 12-bit analogue to digital converters (ADC). These two readings are manipulated by a software package, Lab View. Mathematical manipulation by Lab View converts the two signals into a range in centimetres. The optical set up and the length of the PSD determine that range finder has a range of 20 — 80 cm in the prototype. At these two extremes, the received light spot goes past the ends of the PSD. Over this range accuracy is about 1%.